A STUDY ON EFL STUDENTS' LEVELS OF CRITICAL THINKING SKILLS - Jumariati, Jumariati; Nasrullah, Nasrullah; Sutiono, Cayandrawati; Khairin Utomo, Muhammad (University of Muhammadiyah Malang, 2024)
This research aims to discover the levels of EFL students' critical thinking skills. It is a quantitative approach with descriptive design by utilizing the adapted version of the Watson-Glaser Critical Thinking Skills Test as the instrument. It consists of five indicators: deduction, inference, identifying assumptions, interpretation, and analyzing arguments, with five questions for each. The subjects of the research were 33 students of the English Department of FKIP, Lambung Mangkurat University. The results showed that 23 students (69.69%) had a moderate level of critical thinking skills, seven students (21.21%) had a low level, and three students (9.09%) had a high level. Specifically, they performed low levels in inference and identifying assumptions, but they had moderate levels of critical thinking skills in deduction, interpretation of information, and analysis of arguments. These findings imply the need to facilitate students with more practice to develop their critical thinking skills, particularly in making inferences and identifying assumptions. Further research is recommended to measure EFL students' critical thinking skills by involving larger participants using other instruments of measurement to reveal more conclusive findings.